TRIZ for Shaping Life-Long Learning - Pariyar, Amit; Kulathuramaiyer, Narayanan; Bala, Poline; Man, Chuah Kee (2020 IEEE 8th R10 Humanitarian Technology Conference (R10-HTC), 2020)
The dependence on digital technologies has seen a significant increase during COVID-19 pandemic, to ensure that social connectivity and work goes on, in spite of lockdowns and the physical controls on movement. Though digital learning is expected to create abundant life-long learning opportunities for learners worldwide in this challenging time, there is a danger to further impose inequalities and inadequate access to quality education and life-long learning for the unconnected or poorly connected population. This paper shares our experience of reengineering a MOOC platform as `Community led MOOCs' to serve the learning needs of most under represented single mother communities in Bario - a remote settlement of Kelabits in the Borneo Island of Malaysia. This paper then explores TRIZ based heuristic models to address the socio-technological barriers to lifelong learning and proposes TRIZ principles that can trigger social innovation and creativity in designing lifelong learning solutions for rural communities.
Keywords: Asie; Internet; MOOC; Objectifs de développement durable; Participation; Réservé UdeM; Technologies; Théorie de Résolution des Problèmes Inventifs (TRIZ); numérique